The risk of bleeding complications in patients with cytochrome P450 CYP2C9*2 or CYP2C9*3 alleles on acenocoumarol or phenprocoumon - Visser, Loes E.; van Schaik, Ron H. N.; van Vliet, Martin; Trienekens, Paul H.; De Smet, Peter A. G. M.; Vulto, Arnold G.; Hofman, Albert; van Duijn, Cornelia M.; Stricker, Bruno H. Ch. (Thrombosis and Haemostasis, 2004)
The principal enzyme involved in coumarin metabolism is CYP2C9. Allelic variants of CYP2C9, CYP2C9*2 and CYP2C9*3, code for enzymes with reduced activity. Despite increasing evidence that patients with these genetic variants require lower maintenance doses of anticoagulant therapy, there is lack of agreement among studies on the risk of bleeding and CYP2C9 polymorphisms. It was, therefore, our objective to study the effect of the CYP2C9 polymorphisms on bleeding complications during initiation and maintenance phases of coumarin anticoagulant therapy. The design of the study was a population-based cohort in a sample of the Rotterdam Study, a study in 7,983 subjects. All patients who started treatment with acenocoumarol or phenprocoumon in the study period from January 1, 1991 through December 31, 1998 and for whom INR data were available were included. Patients were followed until a bleeding complication, the end of their treatment, death or end of the study period. Proportional hazards regression analysis was used to estimate the risk of a bleeding complication in relation to CYP2C9 genotype after adjustment for several potentially confounding factors such as age, gender, target INR level, INR, time between INR measurements, and aspirin use. The effect of variant genotype on bleeding risk was separately examined during the initiation phase of 90 days after starting therapy with coumarins. The 996 patients with analysable data had a mean follow-up time of 481 days (1.3 years); 311 (31.2%) had at least 1 variant CYP2C9 allele and 685 (68.8%) had the wild type genotype. For patients with the wild type genotype, the rate of minor bleeding, major bleeding and fatal bleeding was 15.9, 3.4 and 0.2 per 100 treatmentyears, respectively. For patients with a variant genotype, the rate of minor, major and fatal bleeding was 14.6, 5.4 and 0.5 per 100 treatment-years. Patients with a variant genotype on acenocoumarol had a significantly increased risk for a major bleeding event (HR 1.83, 95% CI: 1.01-3.32). During the initiation phase of therapy we found no effect of variant genotype on bleeding risk. In this study among outpatients of an anticoagulation clinic using acenocoumarol or phenprocoumon, having a variant allele of CYP2C9 was associated with an increased risk of major bleeding events in patients on acenocoumarol, but not in patients on phenprocoumon. Although one might consider the assessment of the CYP2C9 genotype of a patient for dose adjustment before starting treatment with acenocoumarol, a prospective randomised trial should demonstrate whether this reduces the increased risk of major bleeding events.
Keywords: Clinical / epidemiological studies; gene mutations; coagulation inhibitors